Experiential Learning in Planning Education : Resources and Tools for Good Practice : Final Report. - Rosier, Johanna; Baldwin, Claudia; Slade, Christine; Perkins, Tim; Coiacetto, Eddo; Budge, Trevor; Harwood, Andrew (Office for Learning and Teaching, 2014)
Final report from a project which developed an integrated package of curriculum activities, assessment and evaluation resources that will support planning educators in delivery of good practice experiential learning. Academics from five Australian tertiary planning schools, led by the University of the Sunshine Coast, collaboratively developed and tested experiential activities and assessments according to a framework based on experiential learning theory. The activities reflected a variety of experiences in the continuum of experiential learning modes, beyond workplace learning, the focus of a previous ALTC project. The framework and associated materials were evaluated through qualitative and quantitative surveys of students, practitioners, and educators to identify materials that achieve key learning principles and contribute to improved student learning outcomes. Inclusive engagement of students, planning practitioners, the Planning Institute of Australia (PIA) as the accrediting body for planning programs, and planning educational staff in other Australian universities occurred.